Islamization of The Concept of Religiosity in Business People - Silva Fauziyah Nadawi; Khoirul Umam (Jurnal Indonesia Sosial Sains, 2024)
This research was motivated by increasing attention to the issue of religious religiosity and ethics in business practices, where the application of religious values is essential to maintain business continuity. This study aims to explore the concept of religiosity from an Islamic perspective by looking at secular elements in Glock and Stark's religiosity and Islamizing the concept to offer a new perspective on Islamic business ethics. Using the literature study method, this study explores the concept of religiosity from a Western perspective, represented by Glock and Stark's theory, and the integration of Islamic elements into pre-existing dimensions. The results show that religiosity in the context of Islam does not only include religious aspects but also involves the application of Islamic values in everyday life. This includes faith, worship, morals, experience, and knowledge. Nevertheless, these adaptations still do not fully reflect the overall characteristics of Islam. This research offers new insights into how religiosity can be applied in business practices from an Islamic perspective.